Positive mental health predicts amelioration of suicidal ideation in patients undergoing cognitive behavioral therapy - Teismann, Tobias; Friedrich, Sören; Margraf, Jürgen (Frontiers in Psychiatry, 2025)
BackgroundPositive mental health has been shown to confer resilience against suicidal ideation and behavior. Yet, studies on treatment seeking populations are rare.The aim of the present study was to investigate, whether PMH predicts the amelioration of suicidal ideation in patients undergoing psychotherapy.MethodData from N = 959 outpatients (61.2% female; age: M(SD) = 36.58 (13.29), range: 18–82 years), who took part in a pretreatment and a posttreatment assessment after 12 sessions of cognitive behavioral therapy, were included. Self-report measures of positive mental health, depression, and suicidal ideation/behavior were used.ResultsPretreatment PMH was shown to predict posttreatment suicidal ideation – after controlling for age, gender, pretreatment depression, suicidal ideation and lifetime suicide attempts.DiscussionPositive mental health might be understood as a protective factor in dealing with suicidal ideation. Findings underscore the need to focus on positive mental health in the risk-assessment and treatment of suicidal patients.